New Indicators for the Mobile Banking Nexus - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose: We make available new critical macroeconomic financial indicators to the research community. Nothing is more powerful than a phenomenon whose time has come. What is the macroeconomic empirical context of growing mobile banking? Perhaps one of the deepest empirical hollows in the financial development literature has been the equation of financial depth in the perspective of money supply to liquid liabilities. This equation has put on the margin, a burgeoning phenomenon whose time has come: mobile banking. Design/Methodology: We decompose financial depth into formal, semi-formal and informal sectors and then assess the incidence of mobile banking on each constituent. Thus the IFS (2008) definition of the financial system is extended to incorporate an informal financial sector in line with Asongu(2011). Three hypotheses based on eight propositions are tested using a plethora of endogeneity-robust and HAC standard errors estimation techniques. Findings: The informal financial sector (a previously missing component in the definition of money supply: M2) is positively affected by mobile banking, while the incidence of mobile banking is negative on formal and semi-formal financial intermediary development. The paper contributes at the same time to the macroeconomic literature on measuring financial development and responds to the growing field of economic development by means of informal financial sector promotion, microfinance and mobile banking. It suggests a practicable way to disentangle the effects of mobile banking on various financial sectors. Research implications: Since empirical research on the phenomenon has been hampered by lack of data, we make available macroeconomic financial indicators to the research community. The present paper is also in response to the numerous calls on the research gap in the literature that emphasize the need for research on mobile banking. The mobile-finance nexus is gaining momentum, yet relatively little scholarly research explores the incidence of these m-banking/m-payment (systems) on financial development. Practical implications: (1) There is a burgeoning role of informal finance in developing countries. (2) The incidence of the growing phenomenon of mobile banking cannot be effectively assessed at a macroeconomic level by traditional financial development indicators. (3) It is a wake-up call for scholarly research on informal financial intermediary development indicators which will guide monetary policy; since a great chunk of the monetary base (M0) in less developed countries is now captured by mobile banking. Originality/value: New financial indicators for mobile banking assessment based on insufficiencies in the financial development literature: liquid liabilities as applied to developing countries is misleading because a great chunk of the monetary base does not transit through the banking system but via informal networks like the growing phenomenon of mobile banking.
Keywords: E00; G20; L96; O17; O33; 330; Banking; Mobile Phones; Shadow Economy; Financial Development; Africa